Studying the content characteristics of New Technology-Based Firms - Boudlaie, Hasan; Mohammadhosein Kenarroodi,; Behrouz Keshavarz Nik, (Technium Social Sciences Journal, 2020)
New technology-based firms (NTBFs) have a significant contribution to economic growth, and in particular to the promotion of innovation and job creation. For this reason, many countries are seeking to establish and grow such institutions using incentive policies. Despite their economic importance, there is no single definition of these companies and several definitions for these types of companies are tailored to the purpose of each study. As for the nature of study, it is important to produce a coherent framework of NTBFs’ characteristics; therefore, the purpose of the present study is to identify the characteristics of NTBFs. For this purpose, the researches that covered the nature of this concept from 1990 to 2011 were analyzed using content analysis. In the first phase, definitions of these companies were compiled; subsequently, effective characteristics were identified to provide a clear nature of these companies. The results of this research led to the identification, confirmation and prioritization of five characteristics, i.e. newness, possessing high-technology, independence, small size in terms of employees and volume of sales, and capital funding by company founders, all of which were prioritized according to the most frequent characteristics in the studied articles. The final result of this study is to guide and streamline future research by achieving theoretical coherence in defining this concept.